Investigações sobre posicionamentos pelo método DGPS usando transmissão das correções diferenciais pelo NTRIP e pelo RDS - Guterres, Silvane Dias da Rosa (2009)
The Global Positioning System (Navstar-GPS) has modernized and allow greater ease in surveys related to activities that require placement in real time. This system consists of a constellation of satellites around the Earth providing a service for 24 hours three-dimensional positioning, velocity and time information to the users. However, certain atmospheric factors and other sources of error can affect the accuracy of GPS receivers. Thus, users can make more precise data collected with the Differential GPS (DGPS). It consists of a network of towers that receive the GPS signals and transmit the signals through fixed radio transmitters. It is effective to support activities which require continuous positioning in real time, which are required accuracies in the order of meters (1 to 3 m). In order for it be a medium to transmit the differential corrections, and the availability of this means there is not always easily and / or economic in Brazil, chose, for the development of this work, the RDS (Radio Data System) and NTRIP (Networked Transport of RTCM via Internet Protocol) for this purpose, using differential corrections transmitted by the format in its implementation DGPSBRDS simplified. It was analyzed statistically and compared it precision and accuracy or standard deviation or mean absolute deviation of the GPS positions with transmission of differential corrections in the RTCM (Radio Technical Commission for Maritime Services) with the surveys carried out by two systems: RDS and NTRIP. They also compared the methods of positioning, the absolute and differential. It was concluded that the differential positioning is obtained more satisfactory results with estimates of precision ranged from 1 to 3 m. The system met the goals of precision and accuracy was NTRIP, which has enabled coordinated in real time with greater accuracy.